Factors Affecting Behavioural Intentions at Hokben Restaurants in Bekasi City - Haryanti, Denny Septa; Hernawati, Nani; Prilyana, Cindy; Sugiharto, Totok (Jurnal Penelitian Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine the influence of Food Quality, Physical Environment Quality, Employee Service Quality, on Behavioral Intentions through Customer Perceived Value, and Customer Satisfaction which influences Pricing for HokBen customers in the city of Bekasi. This research uses primary data by collecting data through questionnaires. This research sample was obtained through a purposive sampling method and obtained 235 respondents. This research uses descriptive statistical methods with the SEM-PLS. The results of this research show that Food Quality and Employee Service Quality have an influence on Customer Perceived Value, while Physical Environment Quality has no influence on Customer Perceived Value, Customer Perceived Value and Pricing have an influence on Customer Satisfaction, and Customer Satisfaction has an influence on Behavioral Intentions.   Keywords: Food Quality, Physical Environment Quality, Employee Service Quality, Customer Perceived Value, Pricing, Customer Satisfaction, Behavioral Intentions